Cognitive and structural cerebral changes in amnestic mild cognitive impairment due to Alzheimer's disease after multicomponent training - Teixeira, Camila Vieira Ligo (Alzheimers Dement (N Y), 2018)
INTRODUCTION: Information about how physical exercise affects patients with amnestic mild cognitive impairment (aMCI) due to Alzheimer's disease (AD) is still missing. This study evaluated the impact of multicomponent exercise training on cognition and brain structure in aMCI subjects with cerebral spinal fluid positive AD biomarkers. METHODS: Forty aMCI subjects were divided in training (multicomponent exercise thrice a week for 6 months) and nontraining groups. Assessments included cardiorespiratory fitness, neurocognitive tests, and a structural magnetic resonance imaging using 3.0 T scanner. FreeSurfer software analyzed hippocampal volume and cortical thickness. RESULTS: The training group showed increased volume in both hippocampi and better performance in episodic memory test after 6 months. In contrast, the nontraining group declined in functional activities, recognition, and cardiorespiratory fitness for the same period. DISCUSSION: Multicomponent exercise seems to improve hippocampal volume and episodic memory, and maintains VO(2max) in aMCI due to AD.